Question #d2a0e

2 Answers
Nov 23, 2017

See below

Explanation:

f(t) = 1/(sqrt(t+1))
f(y^2-1) = 1/(sqrt((y^2-1)+1)) (Replaced t by y^2-1

Simplifying further

f(y^2-1) = 1/(pmy)

f(w-1)^2 = 1/(sqrt((w-1)^2+1)) (Replaced t by (w-1)^2

Simplifying further

f(w-1)^2 = 1/(sqrt(w(w-2)+2)

Nov 23, 2017

See explanation.

Explanation:

color(blue)("Preamble")

f is just a name given to a particular expression construction

The part in the brackets is what is used in that construction at designated points.

f("something") =1/sqrt("something" + 1)

Suppose we have s then

f(s)=1/sqrt(s + 1)

Suppose we have b then

f(b)=1/sqrt(b + 1)

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Answering the question")

f(color(green)(y^2-1))=1/sqrt(color(green)(y^2-1) + 1) = 1/sqrt(color(magenta)(y^2))=1/(+-y)

Note that color(magenta)(y^2) will be a positive value but the square root of a positive value can be either positive or negative
.....................................................................................................

f( color(red)([w-1]^2)) = 1/sqrt(color(red)([w-1]^2)+1) =1/sqrt(w^2-2w+2)

Note that (-1)^2=+1